2011
DOI: 10.1002/ptr.3466
|View full text |Cite
|
Sign up to set email alerts
|

Black Tea Prevents High Fat Diet‐induced Non‐alcoholic Steatohepatitis

Abstract: The chemoprotective actions of aqueous black tea extract (BTE) against high-fat diet (HFD) (60%)-induced non-alcoholic steatohepatitis (NASH) were examined in Wistar rats of both sexes. The results indicated that the HFD rats had higher concentrations of serum glucose, cholesterol, triglycerides, low-density lipoprotein, very low-density lipoprotein, high-density lipoprotein and bilirubin than the corresponding control rats. The enzymes serum aspartate aminotransferase and alanine aminotransferase, which are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
(51 reference statements)
2
6
2
Order By: Relevance
“…As also reported by other investigators 43 44 , we found that DIO mice exhibited higher total and direct bilirubin levels than did Chow controls or DIO mice treated with exogenous bilirubin. The increased bilirubin in DIO animals may reflect blockage of bilirubin excretion due to impaired liver function in these mice.…”
Section: Discussionsupporting
confidence: 91%
“…As also reported by other investigators 43 44 , we found that DIO mice exhibited higher total and direct bilirubin levels than did Chow controls or DIO mice treated with exogenous bilirubin. The increased bilirubin in DIO animals may reflect blockage of bilirubin excretion due to impaired liver function in these mice.…”
Section: Discussionsupporting
confidence: 91%
“…32 Increased NO · production along with changes of antioxidant enzyme status and liver histopathological changes were also observed in non-diabetic high-fat fed rats. 33 Therefore, our data about lack of NO · production increase differ from previously published data. However, it should be noted that published results about NO · concentration measurements in high-fat fed rats confer to usage of indirect methods, such as Griess reaction, when metabolites of nitric oxide nitrate and nitrite (NOx) are assessed or evaluation of nitrotyrosine.…”
Section: Discussioncontrasting
confidence: 99%
“…Increased nitrotyrosine levels were detected in livers of lean female Zucker rats fed with high‐fat diet for short term (4 weeks) . Increased NO · production along with changes of antioxidant enzyme status and liver histopathological changes were also observed in non‐diabetic high‐fat fed rats . Therefore, our data about lack of NO · production increase differ from previously published data.…”
Section: Discussioncontrasting
confidence: 92%
“…These data are in consequence with Singh and Sharma (2011) who reported that pretreatment and posttreatment with CMN prevented histological alterations in liver including marked histological disturbances. Karmakar et al (2011) found that oral administration of aqueous black tea in high fat diet Wistar rats prevented the histological alterations in liver and hepatocellular damage. Therefore, the present data together with the previous data show that supplementation of black tea extract or CMN showed an efficient role in repairing the distortion of the biochemical and histological changes induced by AFB1 in liver.…”
Section: Discussionmentioning
confidence: 99%